"Preheat-parallel" configuration for low-temperature geothermally-fed CHP plants. (15th June 2017) - Van Erdeweghe, Sarah; Van Bael, Johan; Laenen, Ben; D'haeseleer, William
Highlights: We present the novel "Preheat-parallel" CHP fueled by low- T geothermal energy. We consider the connection to a district heating (DH) system. The preheating-effect is the main feature of the "Preheat-parallel" configuration. The preheating-effect is extremely useful for low T return and high T supply  −  T return . Better performance for a 75/50 DH system connection than a parallel or series CHP. Abstract: A novel CHP configuration is presented, which is fueled by low-temperature geothermal energy and delivers heat to a district heating (DH) system.This so-called "Preheat-parallel" configuration has a higher net electrical power output ( W ̇ net ) and a higher exergetic plant efficiency ( η ex ) than the convenient series and parallel configurations for the connection to a state-of-the-art 75/50 DH system.For the considered cases, W ̇ net and η ex are 1.3–6.4% and 0.4–1.9%-pts higher than for the parallel configuration, respectively.The highest values correspond to the highest heat demand.With respect to the series configuration W ̇ net and η ex are 2.1–9.9% and 0.7–3.0%-pts higher, respectively, where the highest values correspond to the lowest heat demand.Furthermore, the optimal CHP configuration - series, parallel or "Preheat-parallel" - is discussed.The optimal configuration depends on the DH system requirements.Supply and return temperatures in the range of T supply = 40 – 110 ° C and T return = 30 – 70 ° C are considered.We conclude that the series and parallel configurations have the best performance for the connection to low-temperature and high-temperature DH systems, respectively.However, for a wide range of T supply and T return, the "Preheat-parallel" configuration is the most appropriate.The preheating -effect is the main feature of the "Preheat-parallel" configuration, and is more useful for a large temperature difference T supply - T return and for low values of T return .Furthermore, we found that for high heat demands and small temperature differences T supply - T return, the "Preheat-parallel" or series configurations might perform better than the parallel configuration for the connection to a high-temperature DH system.